Powerful figures and images: Contribution to Personification of Polis in Hellenistic Art - Mgr. Lucia Novakova (ILIRIA International Review, 2014)
Anthropomorphic symbol in the visual art was an integral part of ancient Greek culture since beginning. Personification of Hellenistic polis, understood as broad and diverse social, geographic and political phenomenon, can be approached by an analysis of archaeological and written sources. Define polis in miscellaneous Hellenistic society is a complex task, especially when socio-historical context is not directly reflected by individual archaeological finds and detailed historical data. Certain changes within political sphere appeared and status of city-states varied. An effort to restore political sovereignty did not expire entirely, therefore personification of poleis from previous period remained in some cases almost unchanged. Personification of political units in Classical art might be similar, distinct or completely different from Hellenistic depictions. Personification of polis in Classical period reflected not only patriotic stance and civil affiliation, but also the legitimacy of state independence. In this aspect, a connection with art of following period may be seen: reshaping of political propaganda was performed during Hellenistic age. Legitimity of state power and expressive means of fine arts were closely related since Archaic period, which occured later in various forms.